Calculation of parameters of radial-piston reducer based on the use of functional semantic networks - Pashkevich V.M.; Mironova M.N. (Научно-технический вестник Брянского государственного университета)
The questions of сalculation of parameters of radial-piston reducer are considered in this article. It is used the approach which is based technologies of functional semantic networks. It is considered possibility applications of functional se-mantic networks for calculation of parameters of radial-piston reducer. Semantic networks to calculate the mass of the radial piston reducer are given.